The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1021/acssensors.8b00287
|View full text |Cite
|
Sign up to set email alerts
|

Nanoplasmonics for Real-Time and Label-Free Monitoring of Microbial Biofilm Formation

Abstract: Microbial biofilms possess intrinsic resistance against conventional antibiotics and cleaning procedures; thus, a better understanding of their complex biological structures is crucial in both medical and industrial applications. Existing laboratory methodologies have focused on macroscopic and mostly indirect characterization of mechanical and microbiological properties of biofilms adhered on a given substrate. However, the kinetics underlying the biofilm formation is not well understood, while such informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 49 publications
(50 reference statements)
1
34
0
Order By: Relevance
“…An interesting optical microsystem for studying biofilm formation in vitro was developed by Funari et al (2018). The authors fabricated what they called a ''nanomushroom-based localized surface plasmon resonance (LSPR) substrate'' for the real-time monitoring of biofilm formation and drug screening.…”
Section: Ll Open Accessmentioning
confidence: 99%
“…An interesting optical microsystem for studying biofilm formation in vitro was developed by Funari et al (2018). The authors fabricated what they called a ''nanomushroom-based localized surface plasmon resonance (LSPR) substrate'' for the real-time monitoring of biofilm formation and drug screening.…”
Section: Ll Open Accessmentioning
confidence: 99%
“…This further decrease is enabled by increasing the sensitivity to bacterial growth because only the first layer of adherent bacteria is probed by the evanescent tail [23,122], therefore affording to probe growth from a much earlier stage. Such configuration lends itself to the study of real-time biofilm growth [125,128], where the bottom layer is crucial, and represents an attractive alternative to traditional cumbersome microscopy or staining protocols [129].…”
Section: Discussionmentioning
confidence: 99%
“…On resonance, the electric field at the surface of the nanoparticle is strongly enhanced and decays with a short distance (tens of nanometre), thereby enabling evanescent-wave optical sensing [123,124]. Funari et al [125] fabricated gold nanoparticles supported by silica pillars, as shown in the sketch in Figure 7(d) and imaged in Figure 7(e). These structures, dubbed gold nanomushrooms, support a broad (Q ≲ 10) LSPR mode which was used to monitor an E. coli biofilm forming over the surface in the presence of different antibiotics.…”
Section: Evanescent Wave-based Astsmentioning
confidence: 99%
“…In the present paper, a simple yet efficient bacterial model based on Escherichia coli is utilized. Recently, it was used to develop a biosensor for detection of catechol [19] and to detect biofilm formation using localized surface plasmon resonance in real-time [20]. Here, we decided to apply an E. coli biosensor based on the MG1655 pKatG-lux strain, which is specific to one of the main reactive oxygen species—hydrogen peroxide (H 2 O 2 ).…”
Section: Introductionmentioning
confidence: 99%